Abdominal Wound Closure in Gynaecological or Obstetrical Surgery with Vicryl® (Polyglactin910) Versus Vicryl Plus® (Polyglactin910 with Triclosan Added): A Comparative Study - Mahaseth, Binod Kumar (Journal of Nepalgunj Medical College, 2019)
Background: Surgical site infection is the most common post-surgical complication in surgical patients. The incidence of surgical site infection varies from 3-20% (or even more) in different part of the world. To date, the best method and material for skin closure has not been recommended by anybody. Triclosan is an antiseptic agent used for coating a suture material to prevent the infections. This case-controlled study was carried out to determine the comparative efficacy of sutures; Objective: This case-controlled study was carried out to determine the comparative efficacy of sutures: vicryl® and vicryl plus® (triclosan, an antiseptic incorporated with suture), in reducing surgical site infection in laparotomy for clean Gyn/Obs operations. Material and method: This case-controlled study was carried out in Dept. Of Gynae/Obs at Nepalgunj Medical College Teaching Hospital, Kohalpur. The period of the study was from Jan 2018 to January 2019. A total of 50 participants were enrolled in the study, who met the inclusion criteria. The patients were divided into two groups A and B, each consisting of 25 patients. The patients were allocated in the groups alternately to remove bias. The Group A consisted of patients where Vicrylplus® (Ethicon, Johnson & Johnson Company, Ahmadabad, India) polyglactin910 with triclosan) was used and Group B consisted of patients where vicryl ® (Ethicon, Johnson & Johnson Company, Ahmadabad, India) polyglactin910 alone) was used. Patients whose abdominal wounds were found infected, pus swab for culture were taken and sent for aerobic culture and sensitivity. All patients received ceftriaxone and metronidazole single dose before operations prophylactically. Result: Surgical site infection ingroup A was 3 cases out of 25 (12%) and in group B it was 6 cases out of 25(24%). Triclosan added polyglactin910 suture found to be statistically non significant concerning prevention of SSI as compared to polyglactin910 (p=0.472). The mean age of the study population was in group A was (29.76±7.47) and in group B was (27.12±7.42).